The synergy of religious education and character education at Madrasah Ibtidaiyah Darul Kirom Bandung - Komara, Endang; Zulvia, Evi; Nurhayati, Yati; Hermawan, Agus (Mitra PGMI: Jurnal Kependidikan MI, 2025)
The purpose of this study was to obtain an overview of the planning, implementation, and supervision of the synergy of religious education and character education at Madrasah Ibtidaiyah Darul Kirom Bandung. This research uses a descriptive method of qualitative approach, and data collection through interview techniques, observation, and documentation studies. The research results showed: (1) Planning the synergy of religious education and character education through the vision and mission of the madrasah in forming students who have noble character, memorize the Qur'an and have global insight. Implementation of the synergy of religious education and character education by habituating students in school time discipline, getting used to praying, saying greetings and kissing the teacher's hand, weekly memorization deposits, congregational prayers and ta'lim activities, and competition activities. Supervision of the synergy of religious education and character education directly by teachers, and indirectly by their respective parents, giving examples, reprimands, weekly assessment notes, and additional study hours.